A comparison of macrophage migration inhibitory factor with C reactive protein in diabetic hypertensive patients with myocardial infarction that underwent primary percutaneous coronary intervention. - Abdullah, Feyan Mirdan; Ghareeb Taher Al-Barzinj, Ruqaya Mohammed (Investigación Clínica, 2020)
The inflammatory response is one of the complications of diabetic hypertensive patients with myocardial infarction (MI). The purpose of this study was to determine the diagnostic value of macrophage migration inhibitory factor (MIF) compared with high sensitivity C reactive protein (hs-CRP) in diabetic hypertensive patients presented with MI; and to determine the concomitant association between these factors in MI patients. For this purpose, 100 patients with MI were categorized into four groups, according to the existence of diabetes mellitus (DM) and/or hypertension (HTN), with 38 subjects with normal angiography considered as the control group. The levels of MIF and hs-CRP were estimated quantitatively using a sandwich enzyme-linked immunosorbent assay and a particle-enhanced immune turbidimetric assay, respectively. In addition, lipid profiles, hematological indicators, and certain clinical features were compared among the studied groups. The levels of MIF and hsCRP increased significantly in MI patients compared to the controls (p<0.05). Additionally, the levels of MIF differed significantly between all MI groups and the control group (p<0.05). Although the group DM-HTN showed the highest MIF level within the MI groups, the difference was not significant (p>0.05). However, the hs-CRP level showed a significant difference (p<0.05). In addition, the MIF level correlated positively with hs-CRP, leukocytes, and neutrophils (p<0.05). Both MIF and hs-CRP levels correlated positively with age, body mass index (BMI), total cholesterol, triglyceride, low-density lipoprotein-cholesterol (LDL-C) and non-high density lipoprotein (HDL), but they correlated negatively with HDL-C. According to the results, although MIF was a valuable diagnostic marker for MI, the hs-CRP showed to be a better prognostic indicator than MIF in diabetic hypertensive patients that presented MI.